Serological biomarkers in autoimmune GFAP astrocytopathy - Fu, Cong-Cong; Huang, Lu; Xu, Lu-Fen; Jiang, Li-Hong; Li, Hui-Lu; Liao, Sha; Yue, Jiajia; Lian, Chun; Yang, Xin-Guang; Long, You-Ming (Frontiers in Immunology, 2022)
Autoimmune glial fibrillary acidic protein astrocytopathy (GFAP-A) is a newly defined meningoencephalomyelitis. The pathogenesis of GFAP-A is not well understood. The present study measured the expression levels of 200 serological cytokines in GFAP-A patients, NMOSD patients and healthy controls (HCs). The correlations between serum cytokine levels and clinical information in GFAP-A patients were analyzed. A total of 147 serological proteins were differentially expressed in GFAP-A patients compared to HCs, and 33 of these proteins were not observed in NMOSD patients. Serum levels of EG-VEGF negatively correlated with GFAP antibody titers, MIP-3 alpha positively correlated with clinical severity in GFAP-A patients, and LIGHT positively correlated with WBC counts and protein levels in the CSF of GFAP-A patients. These results suggest that GFAP and AQP4 astrocytopathy share some common pathology related to TNF signaling. Serum MIP 3 alpha may be a biomarker to assess clinical severity and a potential target for therapy of autoimmune GFAP astrocytopathy.